Excitonic Aharonov–Bohm Oscillations in Core–Shell Nanowires. Issue 3 (20th November 2018) - Corfdir, Pierre; Marquardt, Oliver; Lewis, Ryan B.; Sinito, Chiara; Ramsteiner, Manfred; Trampert, Achim; Jahn, Uwe; Geelhaar, Lutz; Brandt, Oliver; Fomin, Vladimir M.
Abstract: Phase coherence in nanostructures is at the heart of a wide range of quantum effects such as Josephson oscillations between exciton–polariton condensates in microcavities, conductance quantization in 1D ballistic transport, or the optical (excitonic) Aharonov–Bohm effect in semiconductor quantum rings. These effects only occur in structures of the highest perfection. The 2D semiconductor heterostructures required for the observation of Aharonov–Bohm oscillations have proved to be particularly demanding, since interface roughness or alloy fluctuations cause a loss of the spatial phase coherence of excitons, and ultimately induce exciton localization. Experimental work in this field has so far relied on either self‐assembled ring structures with very limited control of shape and dimension or on lithographically defined nanorings that suffer from the detrimental effects of free surfaces. Here, it is demonstrated that nanowires are an ideal platform for studies of the Aharonov–Bohm effect of neutral and charged excitons, as they facilitate the controlled fabrication of nearly ideal quantum rings by combining all‐binary radial heterostructures with axial crystal‐phase quantum structures. Thanks to the atomically flat interfaces and the absence of alloy disorder, excitonic phase coherence is preserved even in rings with circumferences as large as 200 nm. Abstract : Aharonov–Bohm oscillations are observed in the magneto‐photoluminescence spectra of excitons confined in quantum rings in group‐III‐arsenide‐based core–shell nanowires. Rings with nearly ideal interfaces are obtained combining binary radial heterostructures with twin boundaries along the nanowire axis. Thanks to the atomically flat interfaces and the absence of alloy disorder, quantum interferences are detected in rings with circumferences of 200 nm.